(untitled) (Historia, 2021)
Jan Christiaan Smuts (1870–1950) is regarded as one of the two most influential South African leaders of the twentieth century, along with Nelson Rolihlahla Mandela (1918–2013]. While some South Africans regard Smuts as an international statesman, an astute politician, a capable military leader and a brilliant scholar; others maintain that he was a traitor, a jingo, a racist and even an overzealous servant of the British Empire and imperialism. Regardless of these labels, Smuts remains a noteworthy character to this day. He played a leading role in the South African political landscape from 1902 to 1948. He was instrumental in the establishment of the Union of South Africa in 1910. As Minister of Defence, he was crucial in the establishment of the Union Defence Force in 1912 and is regarded as the father of the modern day South African National Defence Force (SANDF). He was actively involved as a combatant and military commander in the Second Anglo-Boer War (1899–1902), as well as the First World War (1914–1918) and the Second World War (1939–1945).